Blood Glucose Evaluation in the Dental Office. Issue 2 (1st May 2013) - Mealey, Brian L.
Abstract : Focused Clinical Question: What role does the dental office play in evaluating blood glucose? Summary: Diabetes and prediabetes are highly prevalent conditions. Although a diagnosis of diabetes or prediabetes can only be done with laboratory glucose testing, the use of in‐office glucose testing may be beneficial. Such testing has been recommended as a means of screening patients for undiagnosed diabetes and for evaluating perioperative glucose levels to minimize risk for medical emergencies during dental treatment. This article reviews the issues that dentists should consider in deciding whether to do glucose testing in the dental office. It focuses on the factors that determine glucose dynamics in people with and without diabetes, provides information to enable interpretation of glucose readings, and offers guidelines for action after glucose testing. This article also discusses regulatory issues related to in‐office glucose testing, a discussion commonly absent from articles on this topic. Conclusions: Evaluation of blood glucose in the dental office may be appropriate for assessing perioperative glucose levels to decrease the risk of adverse hypoglycemic events and potentially for screening patients considered to be at risk for diabetes or prediabetes. Clinicians who choose to perform such in‐office testing must be able to correctly interpret the results, know what steps must be taken based on the findings of the test, and understand the governing regulatory guidelines.